Physicochemical properties, protein conformation, and aggregate morphology of heated myosin from Hypophthalmichthys molitrix and Nemipterus virgatus mixtures. Issue 4 (3rd November 2020) - Yi, Shumin; Ye, Beibei; Li, Jianrong; Wang, Wei; Li, Xuepeng
Abstract: Myosin is a major protein involved in gel formation during the heating process. The physicochemical properties, protein conformation, and aggregate morphology of myosin extracted from mixed Hypophthalmichthys molitrix / Nemipterus virgatus muscle in different ratios (H:N = 1:0, 0:1, 1:1, 1:3, 1:5, 3:1, 5:1) were compared before and after two‐stage heating. The turbidity increased, the reactive sulfhydryl groups became exposed, and the secondary structure of myosin changed from α‐helix to β‐sheet after two‐stage heating. Variations in surface hydrophobicity, tryptophan fluorescence, and ultraviolet spectra demonstrated that there were certain differences in the tertiary structure of mixed myosin. It was noteworthy that mixed myosin aggregated before heating and even formed a more uniform aggregate and crosslinks than other groups after heating when the ratio of H. molitrix and N. virgatus muscle was 5:1. These results suggest that the mixed myosin from different fish species could undergo conformational changes and molecular rearrangement and then form crosslinks and aggregates with diverse sizes during heating process, which would contribute to improve gel characteristics. Abstract :